Application of Geographic Information System (GIS) in PT Pesona Khatulistiwa Nusantara Community Empowerment Initiatives - Fitri Fitri; Seliwati Seliwati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
PT Pesona Khatulistiwa Nusantara (PT PKN) has implemented a Geographic Information System (GIS) to advance its Community Development and Empowerment Program (PPM) and strengthen Corporate Social Responsibility (CSR) practices in pursuit of sustainable development. The system facilitates interactive mapping, spatial data administration, and digital dissemination of PPM activities across education, health, economic, and environmental sectors. The research adopts a qualitative approach combined with Agile development methodology, executed through four sprints between February and May 2025. Development stages encompass user requirement identification, interface design, system construction using Laravel and Leaflet.js, and phased testing through functional and acceptance trials. Eight location points and four program categories were successfully mapped, with usability testing involving ten users yielding favorable outcomes regarding system performance and user experience. Results indicate that GIS integration decreased average information retrieval time from nine minutes (manual reports) to under three minutes while expanding public access to program data. The PPM GIS strengthens transparency, enables participatory monitoring, and supports evidence-based program planning aligned with community needs